ҚАРАҚАЛПАҚ ТИЛИНДЕГИ БИРГЕЛКИЛИ ҚУРАМЛЫ ДӘНЕКЕРСИЗ ҚОСПА ГӘПЛЕРДИҢ ТЕКСТТЕ ЖАЙЛАСЫЎЫ БОЙЫНША ФУНКЦИОНАЛ ТИПЛЕРИ - Халмуратов, Тажетдин Жумашевич (FAN va JAMIYAT, 2026)
The article is devoted to the consideration of functional types of unmarked compound sentences of homogeneous composition in the Karakalpak language in the text.